3D face recognition - Tao, Yue. (2011)
As one of the most successful applications of image analysis, face recognition have been given more and more attention. The applications of face recognition cover various areas. The images used in normal face recognition are usually captured from single source. Thus, face could not be easily recognized if it is captured as side-view. The objective of author’s final year project is to develop a face recognition algorithm using stereo cameras that both front-view face image and side-view face image are valuable for face recognition. The project consists of six small procedures: camera calibration, image capturing, face detection, image merging, image display, and face recognition. The being recognized images could be any front-view face image captured by either left or right stereo camera rigs, or merged front-view face image made by two side-view face images. By incomplete statistic face recognition rate is around 90% with confidence higher than 0.96. In this paper, the motivation and scope of the project will be introduced in chapter one. As well as the introduction of software and programming language used. A short literature review is stated in chapter two. And the procedure with explanations and part of results of the project are described in chapter three and chapter four. At last, chapter five will give a conclusion.